Mendidik Orang Muda Sebagai Antisipasi Dari Dampak Negatif Kemiskinan Menurut Amsal 22:1-16 - Mariana Marice Mau; Herlince Rumahorbo (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
This article describes the importance of youth education and development as an anticipatory measure to overcome the negative impact of poverty. This approach is based on the teaching and wisdom found in Proverbs 22:1-16 in the Bible. In this chapter of Proverbs, the author emphasises the importance of values such as wisdom, work ethics, and wise financial management. By practising these values, young people can build a strong foundation for their future, preventing them from being trapped in the cycle of poverty. Education is identified as one of the key aspects in preparing young people to face the challenges of poverty. A quality education provides the knowledge, skills and awareness needed to solve problems, improve well-being and achieve success in life. In addition, this article highlights the importance of helping young people develop a positive attitude towards work and enterprise. Having a strong work ethic and entrepreneurial skills can help young people overcome economic limitations and create new opportunities to improve their own lives and those of their communities. Wise financial management is also an important factor in preventing the negative impacts of poverty. Young people need to learn about budget management, smart investments, and the importance of saving. By having a good understanding of finance, they can avoid excessive debt and build a stable future. In order to realise effective education and development of young people, there needs to be cooperation between families, educational institutions and communities. Families should prioritise values that support their children's growth and success. Educational institutions should provide inclusive and relevant learning environments, while communities should provide support and opportunities for young people. By adopting this approach, we can anticipate and mitigate the negative impact of poverty on young people. Quality education, a strong work ethic and wise financial management can open the door to a better and more sustainable life for future generations.